.«Exceptional students in Beninese EFL classes: A meta-analytic review of the relationship between teachers’ practices and students’ performance» - FANOU, CODJO CHARLEMAGNE; LANMATCHION, DOSSOU FLAVIEN; MINAFLINOU BANKOLE, ESTELLE SÈYIVÈ (My University, 2015)
Teaching English as a Foreign Language to students with emotional and behavioural disorders in Benin is the key issue in this investigation. The study sets out with the aim to explore teachers’ practices and students’ performance as well as strategies used by Benin EFL teachers to address the issue. The research instruments used are questionnaire, interviews and class observations. The study has revealed that Benin EFL teachers’ practices towards students with special needs are far from enabling them to develop their inner potential and learn effectively. Based on the findings, some strategies have been suggested regarding EFL teaching to such specific students.Cet article se propose d’explorer l’enseignement de l’anglais langue étrangère (ALE) aux apprenants béninois ayant une perturbation émotionnelle ou comportementale. Le principal objectif de cette étude est d’explorer les pratiques des enseignants vis-à-vis de ces types d’apprenants ainsi que les performances de ces derniers. Pour y parvenir, divers instruments tels que les interviews, observations directes et questionnaires ont été utilisés. Des résultats recueillis, il ressort que ce phénomène grandissant ne semble pas retenir l’attention des enseignants d’anglais langue étrangère (ALE) et que de nombreux défis restent à relever. Se basant sur ces résultats, les auteurs de l’article ont fait des suggestions stratégiques pour une prise en charge plus effective de ces types d’apprenants.
Keywords: performance; disorders; emotions; English as a Foreign; Language (EFL); strategy